PENINGKATAN SISTEM MANAJEMEN DAN ANALISIS DATA GERAKAN PRAMUKA KWARCAP BALIKPAPAN - Wiwik Saraswati; Dwi Susilowati; Tamzil Yusuf (Fakultas Ekonomi Universitas Balikpapan, 2023)
The community service activity entitled Improving the management system and data analysis of the Balikpapan kwarcap scout movement is intended to perfect and develop a data analysis system using SPSS and carry out detailed data collection by involving all Kwarcap administrators in the Balikpapan area to standardize the reporting of alert level scout data, fundraisers. , enforcer and guard. The objectives to be achieved from this activity are 1. Knowing the distribution of scout members in Balikpapan 2. Knowing how many scout members are at each level of alert, raiser, enforcer and guard. 3. Facilitate the realization of each activity required.